Study Of The Root Causes Of Children Not Attending School (Ats) In Pemalang District - safari, teti; Marsiska Ariesta Putri; Dimas Adi Wicaksono; Jasman Indradno; Heru Yulianto; Ditho Diva Gansa (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of the study of the Problem of Out-of-School Children (ATS) as one of the triggers of Extreme Poverty and Stunting, this is a section that needs to be discussed because it has an important impact from an educational perspective. The existence of the problem of out-of-school children (ATS) namely economic, moral, and other causes that must be considered not only by the Government but also by the Community itself. This fact was obtained from the results of the Verval of Out-of-School Children (ATS) Data Collection in 2023. Handling ATS requires synergy from all elements of society and stakeholders including the provincial government (Pemprov), district government (Pemkab), legislative institutions, sub-districts, village governments (Pemdes) / kelurahan, civil society organizations, youth organizations, academics, the private sector through the role of the Business World Industry (DUDI) and the community concerned with education. Through this synergy, it is hoped that a commitment and mutual understanding will be built in handling ATS in Pemalang Regency to help the government increase the Human Development Index (HDI) in the field of education and break the chain of poverty between generations.